A NEW APPROACH TO ESTIMATION OF SCIENTIFIC RESEARCH QUALITY - V. I. LEVIN (Высшее образование в России)
The paper highlights the essence of the bibliometric approach to modeling and evaluation of scientific research results, considers the basic foundations of the theory of bibliometric indicators. The baseline data for the evaluation of these indicators are established. The author suggests two universal methods for this evaluation (measuring and the method of moments) and gives some examples of calculating these estimates by means of these methods. The study showed that the calculation of bibliometric indicators is only the first, preliminary stage of the assessment of research results, it should be followed by the expert evaluation.